Determining the number of facilities for large-scale emergency. (1st January 2013) - Meng, Lingpeng; Ma, Qin; Han, Chuanfeng; Wu, Qidi
Classical facility location models like the maximum covering location model implicitly assume that the number of facilities is given exogenously. However, the tremendous magnitude and low frequency of largescale emergencies make it difficult to apply the above assumption simply. This paper developed a greedy clustering method aiming to identify suitable number of large-scale emergency facilities, taking into account of the distinct attributes of each demand area and the required response quality. An illustrative example is given to show the effectiveness and efficiency of the proposed method.